The impact of sharia financing on economic growth and key economic indicators in Sulawesi - Yunus, Rita; Akbar, Muhammad; Wijaya, Fajar (LPPM ISNJ Bengkalis, 2025)
Purpose – This study aims to analyze the impact of sharia financing on economic growth (GDP), inequality, poverty, productivity, and school participation rates in the province of Sulawesi, Indonesia. Method – This study uses a quantitative approach with a data panel regression method and a fixed effects model. The data used included data from the annual report published by the Central Statistics Agency (CSA) and the Financial Services Authority (FSA) for the 2015-2023 period from 6 provinces in Sulawesi, with 54 observational data. Findings – The study results show that sharia financing positively affects economic growth (GDP), poverty, productivity, and school participation in Sulawesi. However, sharia financing does not affect income inequality. Overall, these findings indicate that sharia financing can drive more inclusive and sustainable economic growth. Implications – The implications of these findings contribute to the theory of sharia finance by enriching the literature on the role of inclusive finance that can support social justice and equitable economic growth. From a practical point of view, these findings demonstrate the need for governments and financial institutions to prioritize a fairer distribution of sharia financing, especially in underserved areas, to help reduce poverty and inequality and increase economic growth, productivity, and access to education.